Model Identification of Traveling Wave Ultrasonic Motor Using Step Response - Shi Jingzhuo; Zhang Caixia (Institute of Advanced Engineering and Science, 2014)
Ultrasonic motor’s model adapting to control application is the foundation of the motor’s high performance control. Ultrasonic motor’s frequency-speed control model gives a signification to improve speed control performance. This paper shows the design of stepping response experiments, and also explains the model identification of USM by the way of characteristic point method. Considering its time-varying characteristic, model parameters can be fitted using functions with the independent variable is frequency or speed. Consequently, non-linearity can reflect in speed control model appropriately.